Novel approach to solving stochastic constrained shortest path problem with quantum computing - Yang, Richard Chen Xiao (Nanyang Technological University, 2023)
This thesis presents a new approach to tackling the stochastic constraint shortest path problem by using a quasi-optimal quantum algorithm. These problems are highly relevant in the real world, with broad applications in areas like transportation, logistics, and network optimization. We start the thesis by outlining the problem, explaining the limitations of traditional methods, and introducing the background information necessary to understanding our proposed algorithm. Then, we present our quantum-based solution and experiment results.